2021
DOI: 10.1177/1942602x211037260
|View full text |Cite
|
Sign up to set email alerts
|

The Vital Role of the School Nurse in Managing Asthma

Abstract: Since asthma is the most common noncommunicable chronic childhood disease in the United States, school nurses will encounter students with this health condition. The purpose of this article is to present the school nurse as the leader in directing the management of a student’s chronic health condition at school. This article provides a table of resources and discusses many aspects of asthma management, including utilization of the student’s asthma action plan, student-specific school accommodation needs, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The articles included have made it possible to describe the advantages of the health figure of the school nurse in the management of chronic pathologies and disabilities and the development of personalized plans for the condition of the child. The studies analyzed revealed the role of the nurse to develop an Individual Health Plan, aimed at students suffering from chronic conditions such as autism (Lucas et al, 2020), asthma (Russell et al, 2022), and epilepsy (Dean et al, 2021). The school nurse, together with the multidisciplinary education team, identifies, evaluates, and monitors students who may be eligible for services through the Individuals with Disabilities Education Improvement Act or Section 504 of the Rehabilitation Act (Section 504 under the Rehabilitation Act, 1973).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles included have made it possible to describe the advantages of the health figure of the school nurse in the management of chronic pathologies and disabilities and the development of personalized plans for the condition of the child. The studies analyzed revealed the role of the nurse to develop an Individual Health Plan, aimed at students suffering from chronic conditions such as autism (Lucas et al, 2020), asthma (Russell et al, 2022), and epilepsy (Dean et al, 2021). The school nurse, together with the multidisciplinary education team, identifies, evaluates, and monitors students who may be eligible for services through the Individuals with Disabilities Education Improvement Act or Section 504 of the Rehabilitation Act (Section 504 under the Rehabilitation Act, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in North Carolina, between 2006 and 2016, shows a statistically significant increase in the occurrence rate of some chronic health conditions, such as asthma and type 1 diabetes, with a consequent increase in nurse-led health consultations especially for diabetes; the study made it possible to understand which pathologies required the activation of health services within the school context (Best et al, 2021). Asthma is the leading cause of school absenteeism due to chronic illness (Gibson-Young et al, 2022; Russell et al, 2022). School nurses perceive themselves as competent in asthma education and management in schools (Gibson-Young et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation